2015
DOI: 10.1089/tmj.2014.0152
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mental Health Diagnoses Treated via Interactive Video and Face to Face in the Veterans Healthcare Administration

Abstract: Providers and patients may feel more comfortable treating depression and anxiety disorders than substance use or psychosis via interactive video.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…By reviewing and using the information obtained from the review of 15 similar articles,[1356910121517192127282930] requirements of TMH services were identified and a questionnaire was developed for the validate necessary TMH services. The questionnaire consisted of 2 parts and 29 questions, including demographic information (5 questions), and identified TMH service requirements (24 questions), which were based on the 5-point Likert scale (very much, much, no idea, low, and very low).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By reviewing and using the information obtained from the review of 15 similar articles,[1356910121517192127282930] requirements of TMH services were identified and a questionnaire was developed for the validate necessary TMH services. The questionnaire consisted of 2 parts and 29 questions, including demographic information (5 questions), and identified TMH service requirements (24 questions), which were based on the 5-point Likert scale (very much, much, no idea, low, and very low).…”
Section: Methodsmentioning
confidence: 99%
“…[4] Studies show that survivors of war and their families suffer from a wide range of mental disorders such as posttraumatic stress disorder (PTSD), mood disorders and anxiety, aggression, conflict, and depression. [56] According to the Mental Disorders Research Center of the Foundation of Martyrs and Veterans Affairs, more than 85% of the participants in the Iran–Iraq War has psychological symptoms of PTSD. [7]…”
Section: Introductionmentioning
confidence: 99%
“…12 Tele-therapy has been trialled in US and Canadian veterans using a variety of treatment methods, such as prolonged exposure, [13][14][15][16][17] CBT [18][19][20][21] and cognitive processing therapy (CPT). [22][23][24][25][26][27] Despite this evidence, remote-access interventions are not routinely offered to veterans with PTSD in the UK. The current study is part of a wider project investigating the acceptability and feasibility of teletherapy with UK veterans, with recently published findings suggesting that it is acceptable to those accessing the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to treatment of depression, the evidence base for telepsychiatry is particularly strong [31]. A number of studies have reported greater symptom improvement when comparing telemental health groups to in-person groups.…”
Section: Introductionmentioning
confidence: 99%